Penerapan Model Discovery Learning dengan Pendekatan Diferensiasi Menggunakan Google Classroom untuk Meningkatkan Hasil Belajar IPA - Cahyono, Didik (Jurnal Pendidikan Edukasi Kusuma Bangsa, 2024)
earning using the discovery learning learning model. Based on the results of observations during science learning in class IX-A at Junior State High School 3 Batu Ampar, information was obtained that student learning outcomes were still low because after the Covid-19 pandemic, students' learning motivation had decreased, teachers rarely implemented interactive learning, so learning was less interesting. This research aims to improve science learning outcomes with a differentiation approach using Google Classroom. The type of research used is classroom action research which consists of 3 cycles. This research was carried out at State Junior High School 3 Batu Ampar, Kubu Raya Regency with the research subjects being students in class IX-A. This research data is the implementation of learning, student learning outcomes, and student responses in learning. The research instruments used were computer based tests (CBT) and observation sheets to measure learning implementation, learning outcomes, and student responses to learning using the discovery learning learning model. Data was analyzed by reducing and percentageing the data. The final stage is the reflection stage to determine whether to continue the research or not. Based on the results of the research that has been carried out, an increase in data from cycle I, cycle II, and cycle III was obtained regarding the implementation of the discovery learning learning model, science learning outcomes, and student responses